(untitled) (Research, Society and Development, 2022)
Introduction: The endodontic treatment aims to promote cleaning and shaping of the root canal, during the stages of endodontic treatment, some accidents and complications may occur, with endodontic instrument fracture being a prominent recurrent accident. Objective: To describe a clinical case report about an endodontic treatment with the occurrence of file fracture. Methods: The present work consists of a clinical case report, analyzed through scientific knowledge in endodontics, with the relevance of observing the occurrence of an accident during the root canal procedure, as well as a way to circumvent this unforeseen situation and achieve a satisfactory result. Results: According to the clinical diagnosis, endodontic treatment was chosen in a single session, which was later performed, with the presence of an endodontic accident of a file fracture, which was circumvented using the technique of passing the file. Conclusions: considering the result proceeds in the clinical case presented, it is concluded that a proposed technique of overtaking the file represents a safe and viable alternative, allowing to continue the endodontic treatment and providing opportunities for the achievement of therapeutic success.